1994
DOI: 10.7326/0003-4819-120-2-199401150-00007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Computer-based Clinical Decision Support Systems on Clinician Performance and Patient Outcome: A Critical Appraisal of Research

Abstract: Strong evidence suggests that some CDSSs can improve physician performance. Additional well-designed studies are needed to assess their effects and cost-effectiveness, especially on patient outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
307
2
2

Year Published

1997
1997
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 599 publications
(313 citation statements)
references
References 0 publications
2
307
2
2
Order By: Relevance
“…Compared with other existing approaches of clinical decision support systems, such as reminder system and computerised physician order entry system (McDonald, 1976;Johnston et al, 1994;Elson & Connelly, 1995;Bates et al, 2001), this approach and result has demonstrated a better pathway knowledge support in the whole treatment process as well as better improvement in medical error and length of stay. Moreover, this study also contributes to the design approach of the socio-technical system by integrating the informal, formal and technical levels in the organisation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with other existing approaches of clinical decision support systems, such as reminder system and computerised physician order entry system (McDonald, 1976;Johnston et al, 1994;Elson & Connelly, 1995;Bates et al, 2001), this approach and result has demonstrated a better pathway knowledge support in the whole treatment process as well as better improvement in medical error and length of stay. Moreover, this study also contributes to the design approach of the socio-technical system by integrating the informal, formal and technical levels in the organisation.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, IT has been recognised by many researchers as a useful tool for clinical decision support. They are used to improve medical performance and pathway compliance by delivering relevant advice in a timely manner (Johnston et al, 1994;Elson & Connelly, 1995). These capabilities rely on the structured clinical data and rules that trigger appropriate recommendations (Zielstorff, 1998;Lenz & Reichert, 2005).…”
Section: Related Researchmentioning
confidence: 99%
“…Overall, it seems that systems that are problem-orientated, and systems that serve to alert and remind, have a better success than large diagnostic ones [14,23]. Our system does not interfere with the whole diagnostic process.…”
Section: Discussionmentioning
confidence: 86%
“…While it is clear that no computer system can replace the physician and her complex reasoning about the patient's state, the positive effect of clinical guidelines on medical practice has been demonstrated by several studies [1].…”
Section: Introductionmentioning
confidence: 99%